LA POBREZAFILIA. LA PORNIFICACIÓN DE LA POBREZA EN AMÉRICA LATINA - Sequeira Rovira, Paula (Universidad de Costa Rica, 2022)
This article aims to discuss about povertyphilia (pobrezafilia), that is to say, the sensualized photographic exhibition of women in poor housing in Latin America. In these images, the setting that shows the lower social class of its protagonists is even more important than the bodies of these young women. To carry out the analysis, various images that appeared on the internet under this descriptor were studied, as well as other documents that have served to contextualize part of the antecedents related to the production of desire for this type of erotic images.